Incidence and prevalence of communicative disorders in a midsouthern public school system in U.S.A. - James Monroe Stewart (Journal of All India Institute of Speech and Hearing, 1970)
This study evaluated incidence and its demography in the Nashville public schools in grades K through 12 for the academic years 1978-79 through 1981-82. The Board of Education supplied the data on all children identified with communicative disorders, which included the served, underserved, and unserved. The results indicated an average enrollment decline of 3.24% and an average prevalence of 2.95% for primary communicative disorders in the school population. Incidence figures declined from 8.09 to 1.19%, and revealed a higher number of blacks and others than whites. The results also differentiated the gross and net incidences.